How municipalities should approach the transformation of public spaces - Michaela Malá; Martina Sýkorová; Licia Felicioni (Acta Polytechnica CTU Proceedings)
Public spaces are the living rooms of cities, accessible to everyone without any restrictions. Public spaces are the calling card of the city; they are where the community comes together. Their design either enables or complicates community life. From a visitor's point of view, public spaces are the first things to be noticed and encountered in a city. Due to various circumstances, public spaces sometimes fail to meet the abovementioned features or do not fulfil them to the degree they should. Thus, the presented methodology guidelines may help small cities representatives who do not have the professional or personnel capacity to deal with public spaces through planning, preparation and contracting the public spaces studies, which leads to a quality assessment of public spaces. The guidelines also include tips for improving public spaces, recommended practices for public participation in planning the transformation of public areas, and a site assessment form for a non-expert's perspective.